Sex Differences in the Anxiolytic Properties of Common Cannabis Terpenes, Linalool and β-Myrcene, in Mice - Jasmin K. Wagner; Ella Gambell; Tucker Gibbons; Thomas J. Martin; Joshua S. Kaplan (NeuroSci)
Volatile organic compounds, colloquially referred to as “terpenes”, have been proposed to impact the therapeutic qualities that are traditionally ascribed to cannabis. However, the contribution of these terpenes in anxiety, at relevant levels and exposure methods common with cannabis use, is lacking empirical assessment. We tested the anxiolytic properties of two prominent cannabis terpenes, linalool and β-myrcene, in male and female mice using short duration vapor pulls to model human inhalation when combusting flower or vaping cannabis oil. We observed sex differences in the locomotor effects in the open field and anxiolytic properties in the elevated plus maze of these terpenes that depended on their exposure characteristics. Both linalool and β-myrcene had anxiolytic effects in female mice when delivered in discrete vapor pulls over the course of 30 min. In male mice, only a single vapor hit containing linalool or β-myrcene had anxiolytic effects. The combination of sub-effective levels of linalool and the phytocannabinoid, cannabidiol (CBD), had synergistic anxiolytic effects in females, but these entourage effects between CBD and terpenes were absent with β-myrcene for females and for either terpene in males. Together, our findings reveal sex differences in the anxiolytic properties of common cannabis terpenes and highlight the potential benefits of unique combinations of CBD and terpenes in expanding the therapeutic dose window.